Prevalence and intensity of helminth parasites in House geckos (Hemidactylus frenatus) of Dhaka City, Bangladesh (Bangladesh Journal of Zoology, 2025)
The Asian house gecko (Hemidactylus frenatus) is a unique species among lizards, commonly found in human habitats and often regarded as a pest. Like all vertebrates, these geckos are susceptible to parasites.  In this investigation, a total of 54 H. frenatus specimens were collected from randomly selected households in various locations throughout Dhaka city to examine parasitic infections. The study's results revealed that 61.11% of the geckos were infected with endoparasites. The infection rate for female geckos (63.64%) was higher than that for males (59.38%). A total of 61 parasites were collected from different organs including the body cavity, stomach, intestine, and lungs of the house geckos. Four species of parasites were identified, belonging to the groups trematode (Ganeo kumaonensis), nematoda (Strongyloides cruzi and Neopharyngodon gecko), and pentastomida (Raillietiella frenatus). Notably, the pentastomid Raillietiella frenatus had not been previously recorded in H. frenatus in Bangladesh. The prevalence of the identified parasites was as follows: Ganeo kumaonensis (9.26%), Strongyloides cruzi (7.41%), Neopharyngodon gecko (37.04%), and Raillietiella frenatus (18.52%). Among these, the nematode exhibited the highest prevalence at 44.44%, while the trematode showed the lowest at 9.26%. A significant number of parasites were also collected from the stomach, accounting for 27.78% of the total. Additionally, when examining various length groups, those geckos measuring 9.5-10.49 cm in length showed a higher susceptibility to parasitic infections (88.23%) compared to other length groups. Similarly, in different weight groups, geckos weighting 2.5-3.49 grams were found to have a higher susceptibility to parasitic infections (78.12%). Furthermore, a positive correlation was observed between the host's weight and the parasite burden. The significance of the current study lies in identifying the parasites that infect this unique species within the study area.Bangladesh J. Zool. 53(1): 57-66, 2025